Hydrothermal Alteration and Mineralization of the Randu Kuning Porphyry Cu-Au and Intermediate Sulphidation Epithermal Au-Base Metals Deposits in Selogiri, Central Java, Indonesia - Sutarto Sutarto; Arifudin Idrus; Agung Harijoko; Lucas Donny Setijadji; Franz Michael Meyer; Sven Sindern; Sapto Putranto (Journal of Applied Geology, 2016)
The Randu Kuning Porphyry Cu-Au prospect area is situated in the Selogiri district, Wonogiri regency, Central Java, Indonesia, about 40 km to the South-East from Solo city, or approximately 70 km east of Yogyakarta city. The Randu Kuning area and its vicinity is a part of the East Java Southern Mountain Zone, mostly occupied by both plutonic and volcanic igneous rocks, volcaniclastic, silisiclastic and carbonate rocks. Magmatism-volcanism products were indicated by the abundant of igneous and volcaniclastic rocks of Mandalika and Semilir Formation. The Alteration zones distribution are generally controlled by the NE–SW and NW–SE trending structures. At least eight types of hydrothermal alteration at the Randu Kuning area and its vicinity had been identified, i.e. magnetite + biotite ± K-feldspar ± chlorite (potassic), chlorite + sericite + magnetite ± actinolite, chlorite + magnetite ± actinolite ± carbonate (inner propylitic), chlorite + epidote ± carbonate (outer propylitic), sericite + quartz + pyrite (phyllic), illite + kaolinite ± smectite (intermediate argillic), illite + kaolinite ± pyrophyllite ± alunite (advanced argillic) and quatz + chlorite (sillisic) zones. The Randu Kuning mineralization at Selogiri is co existing with the porphyry Cu-Au and intermediate sulphidation epithermal Au-base metals. Mineralization in the porphyry environment is mostly associated with the present of quartz-sulphides veins including AB, C, carbonate-sulphides veins (D vein) as well as disseminated sulphides. While in the epithermal prospect, mineralization is particularly associated with pyrite + sphalerite + chalcopyrite + carbonate ± galena veins as well as hydrothermal breccias. The Randu Kuning porphyry prospect has copper gold grade in range at about 0.66–5.7 gr/t Au and 0.04–1.24 % Cu, whereas in the intermediate sulphidation epithermal contain around 0.1–20.8 gr/t Au, 1.2–28.1 gr/t Ag, 0.05–0.9 % Zn, 0.14–0.59 % Pb and 0.01–0.65 % Cu.